2020
DOI: 10.1111/joss.12594
|View full text |Cite
|
Sign up to set email alerts
|

The free listing task for describing the sensory profiling of dairy foods: A case study with microfiltered goat whey orange juice beverage

Abstract: The sensory profiling using free listing task and consumer acceptance of a goat whey orange juice (GWOJ) beverage processed by microfiltration (20, 30, 40, and 50 C) or conventional pasteurization were investigated. Free listing task allowed the discrimination of the beverages based on the type of processing (pasteurization or microfiltration) and microfiltration temperature. The pasteurized beverage had yellow color, orange aroma and flavor, and a more viscous texture, whereas the microfiltered beverages had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 28 publications
(57 reference statements)
1
21
0
Order By: Relevance
“…The squid samples did not need other pretreatments, so only the professionalism and consistency of the evaluation were considered in the sensory assessment, ignoring the importance of consumers’ demand for the product. Consumers’ perceptions can be used for the assessment in the product development, which can significantly save time and labor costs (Vieira et al., 2020). It also suggested that evaluation based on preferred attribute elicitation methodology had the advantage of providing data on the importance of attributes for product acceptance (da Costa et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The squid samples did not need other pretreatments, so only the professionalism and consistency of the evaluation were considered in the sensory assessment, ignoring the importance of consumers’ demand for the product. Consumers’ perceptions can be used for the assessment in the product development, which can significantly save time and labor costs (Vieira et al., 2020). It also suggested that evaluation based on preferred attribute elicitation methodology had the advantage of providing data on the importance of attributes for product acceptance (da Costa et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In commercial products, the fat values in Mascarpone were 40% (Almeida et al, 2018), 42% (Kapetanakou et al, 2017) 42.5% (Carvalho et al, 2015) and from 33.3 to 49.8% (Buratto, 2010), results slightly below those observed in the present study, The free word association method and the completion task can be useful to comprehend the thoughts and feelings about food products and can be explored by the dairy industry in making more competitive products (Judacewski et al, 2019;Torres et al, 2020). The free listing task and preferred attribute elicitation methodologies do not require previous training and allow to assess the perceptions of consumers of dairy products and to develop derivatives with appropriate sensory attributes, in addition to efficient marketing strategies for their commercialization (Soares et al, 2019;Vieira et al, 2020).…”
Section: Resultsmentioning
confidence: 62%
“…Therefore, QDA can be helpful in a detailed description of the negative and positive aspects of honeys, adulteration of honeys, and their right classification. QDA requires a trained panel and it is time-consuming, therefore in the future some other method could be used to evaluate honey sensorial features as proposed by G ambaro et al ( 2019)-word association (WA) and product personality profiling (PPP) of consumer perception of deodorant, conjoint analysis and focus group established by Pires et al (2019) to study consumers' perceptions and acceptance of bologna sausage, and/or free listing task used by Vieira et al (2020) to the sensory profiling of microfiltered goat whey orange juice beverage.…”
Section: Discussionmentioning
confidence: 99%